2006
DOI: 10.1111/j.1365-2656.2006.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Odour‐mediated long‐range avoidance of interspecific competition by a solitary endoparasitoid: a time‐saving foraging strategy

Abstract: Summary 1.In studies on optimal foraging strategies, long-range decisions in the pursuit of resource are rarely considered. This is also the case for sympatric parasitoids, which may be confronted with the decision to accept or reject host larvae that are already parasitized by a competing species. They can be expected to reject already parasitized hosts if it is likely that they will lose the resulting intrinsic competition. However, examples of such interspecific host discrimination are rare. 2. We propose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 67 publications
3
31
0
Order By: Relevance
“…When the time interval between the two ovipositions is very short, the survival of equally aged parasitoid larvae is independent of the oviposition sequence ( Bai & Mackauer, 1991;Mackauer et al , 1992;Tamò et al , 2006 ). For this purpose, individual aphids isolated on a piece of wheat leaf were offered to an A. rhopalosiphi female.…”
Section: The Outcome Of the Larval Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the time interval between the two ovipositions is very short, the survival of equally aged parasitoid larvae is independent of the oviposition sequence ( Bai & Mackauer, 1991;Mackauer et al , 1992;Tamò et al , 2006 ). For this purpose, individual aphids isolated on a piece of wheat leaf were offered to an A. rhopalosiphi female.…”
Section: The Outcome Of the Larval Competitionmentioning
confidence: 99%
“…In the case of multi-parasitism, parasitoid larvae compete for the possession of the host by physical fights or physiological suppression, leading to the death of supernumerary immatures ( Salt, 1961;Bai & Mackauer, 1991;Godfray, 1994 ). Until now, only a few studies have addressed the question of the effect of interspecific competition on the foraging strategies of parasitoids ( Vet et al , 1984;McBrien & Mackauer, 1990;Janssen et al , 1995;Takasu et al , 1998;Tamò et al , 2006 ). Females may interact directly (interference competition), by attacking and chasing other parasitoids arriving on the patch ( Godfray, 1994;Fields et al , 1998 ), or, more often, indirectly by reducing the proportion of healthy hosts available for the others (exploitative competition).…”
Section: Introductionmentioning
confidence: 99%
“…Avoidance of conspecific competitors has been reported for parasitoid species, but few studies have focused on avoidance of heterospecific competitors. In arthropods, avoidance of heterospecific competitors has been demonstrated in bark beetles (Byers 1993), phytophagous mites (Pallini et al 1997), predatory mites Gnanvossou et al 2003), and parasitoids (Janssen et al 1995;Tamo et al 2006;Cancino et al 2012). However, avoidance is not always systematic (Janssen et al 1999) and avoidance mechanisms are often not clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…The larval parasitoid C. sonorensis, like many others of its kind, relies on volatiles emitted by caterpillar-damaged plants to locate hosts (Elzen et al 1983;McAuslane et al 1991;Tamò et al 2006). Chelonus insularis is an egg-larval parasitoid and could use cues coming directly from the eggs and traces of pheromones or other chemicals left by ovipositing females to locate host eggs, but evidence is mounting that eggs, once deposited on plants, may also trigger the emission of volatiles by plants that attract egg parasitoids (reviewed by Fatouros et al 2008).…”
Section: Introductionmentioning
confidence: 99%